A Field Study on the Arching Behavior of a Geogrid-Reinforced Floating Pile-Supported Embankment. (November 2022) - Pan, Gaofeng; Liu, Xianfeng; Yuan, Shengyang; Wang, Yibo; Sun, Danxi; Feng, Yan; Jiang, Guanlu
Highlights: The soil arching effect of floating-pile pile-supported embankment structure will undergo multi-stage evolution. The reduction of the pile-soil differential settlement will not lead to the weakening of the soil arching effect. Differential settlement of pile-soil, adjacent pile space and subgrade height jointly determine the development stage of soil arching. The filling height corresponding to the minimum pile-soil settlement ratio is recommended as the critical filling height Hcri for the soil arching effect. Abstract: Geogrid-reinforced floating pile-supported (GRFPS) embankments are widely used in areas with moderately compressed soil. Due to the interaction among foundation soil, suspended piles and geogrids, the characteristics of stress and deformation are very complicated. In this paper, a field filling test of GRFPS embankments with two pile lengths (L = 8 m, 15 m), S1 and S2, was carried out in areas with moderately compressed soil. The evolution of soil arching, deformation of soil, piles and geogrids during the construction and equilibrium stage of embankments were monitored. Results show that with the increasing of filling height, there were three stages for the evolution soil arching: no soil arching, formation of soil arching, and stabilization of soil arching. When the pile-soil settlement ratio η reached its minimum value, soil arching formed, and the differential settlement between pile and soil at the top of pile cap (Δδ) was around 1% of the net pile spacing ( s - d, where s is the pile spacing, d is the diameter of pile cap). The corresponding critical filling heights ( H cri ) were 1.4 ( s - d ) and 3( s - d ) for S1 and S2, respectively. The strain of geogrid mainly developed during the initial stage of filling with the development of Δδ. When the filling height was larger than 5.2 m, the magnitude of soil arching was larger for the embankment with longer pile length (S2). Meanwhile, for S2, the soil arching coefficient Cc gradually transited from friction piles into the end-bearing piles with the increasing filing height of the embankment. The strain of the geogrid mainly occurs in the initial stage of filling (t < 75 d), mainly due to the differential settlement between the pile and soil. After that, the overall settlement of the composite foundation also slightly caused the strain of the geogrid. Finally, three states of soil arching effects of the GRFPS embankment and the evolution characteristics of each index under different states are proposed. This case study provides an enhanced understanding of the performance GRFPS embankment.